The effect of microwave charcoal activation on the calorific value and burning rate of palm kernel shell charcoal briquettes - Raharjo, Sapto; Lestari, Lina; Sudiana, I Nyoman; Rusman, La Ode; Sulastri, Niken (Edelweiss Applied Science and Technology, 2025)
This experimental study aims to determine the effect of microwave charcoal activation parameters on the calorific value of palm kernel shell charcoal briquettes. The study was carried out in several stages, specifically collecting and drying the raw materials, carbonizing, grinding and sifting, activation, mixing adhesives, pressing, and drying. Palm kernel shell charcoal briquettes are made using sago as an adhesive with a mass ratio of 9:1. Charcoal granules are sieved using an 80-mesh size. The activation was performed using a microwave at 150 W with variations in activation time of 360, 480, and 600 seconds. The charcoal was also activated for 480 seconds at 70 watts, 150 watts, and 230 watts. The sample was compressed at a pressure of 9.31 x 106 N/m². The calorific value and burning rate of charcoal briquettes without activation are 6948.74 cal/g and 0.084 g/min. Microwave activation of charcoal can increase the calorific value of briquettes to 8015.14 cal/g and decrease the burning rate to 0.046 g/min at 230 watts of power and 480 seconds of time. The decrease in burning rate indicates that the briquettes are more efficient. SEM tests proved the change in diameter and number of pores, which are traces of volatile matter vaporized during charcoal activation, leading to an increase in calorific value and a decrease in combustion rate. The EDS test shows that the palm kernel shell charcoal briquettes do not contain sulfur, indicating that they are safe to use as fuel and environmentally friendly.